The Factors That Influence The Use Of Maternal And Child Health Books In Mothers - Riski Candra Amalia; Asruria Sani Fajriah; Santy Irene Putri (Poltekkes Kemenkes Surakarta, 2022)
Background: The MCH Book is a tool for the early detection of any disturbances or health problems for mothers and children. This book is important, but its use is not optimal. The purpose of this study was to determine and analyze the factors that influence the use of maternal and child health books by mothers. Methods: This study uses an analytic observational design with a cross-sectional approach with a sampling technique using an accidental sampling technique with a sample of 78 people. Respondents were selected who met the age of 22–40 years, could read and write, and were willing to be respondents. This study used a research instrument in the form of a questionnaire and was measured using a scale. The data was analyzed by multiple linear regression tests using SPSS for Windows version 22. Results: Variable knowledge and attitudes together (simultaneously) have a significant effect on the utilization of MCH books. The results of the statistical test obtained p value = 0.021 on the knowledge variable, p = 0.000 on the attitude variable, where p < (0.05). Conclusion: There is a relationship between knowledge and attitudes of the millennial generation of pregnant women towards the use of MCH books at the Pacar Keling Health Center. It is hoped that millennial-generation pregnant women will not only seek information about health through social media/the internet but also by reading and understanding the contents of the MCH book.